2022
DOI: 10.1186/s12978-022-01372-3
|View full text |Cite
|
Sign up to set email alerts
|

Health workers’ and hospital administrators’ perspectives on mistreatment of women during facility-based childbirth: a multicenter qualitative study in Ghana

Abstract: Background Globally, mistreatment of women during facility-based childbirth continues to impact negatively on the quality of maternal healthcare provision and utilization. The views of health workers are vital in achieving comprehensive understanding of mistreatment of women, and to design evidence-based interventions to prevent it. We explored the perspectives of health workers and hospital administrators on mistreatment of women during childbirth to identify opportunity for improvement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…19 approximately 90% of pregnant women receive four or more antenatal visits in Ghana. 20 NFHS-5 district (Aligarh) fact sheet reported 44.7% mothers had at least 4 ANC visits. 21 About 60 % women received at least one ANC by skilled health professionals, of them >80% had four or more ANC visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 approximately 90% of pregnant women receive four or more antenatal visits in Ghana. 20 NFHS-5 district (Aligarh) fact sheet reported 44.7% mothers had at least 4 ANC visits. 21 About 60 % women received at least one ANC by skilled health professionals, of them >80% had four or more ANC visits.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported 73.5% coverage of institutional deliveries better than Ethiopia (14.4%), (71%) and (20.5%) but lesser than Aligarh (82.6%), Ghana (80%) and East Godavari district (86%). [19][20][21][24][25][26] Better uptake of INC was probably due to increase in awareness regarding safe delivery practices due to regular contact with health workers and provision of monetary incentive under JSY and free of cost facilities through JSSK.…”
Section: Discussionmentioning
confidence: 99%
“…This is how things are. This is how they should be and how they would be if we simply allowed them to do so [9].…”
Section: Birth Is a Natural Event -So It Should Work Naturallymentioning
confidence: 99%
“…Other studies in Ghana have found obstetric violence to be highly pervasive in institutional deliveries with a prevalence rate of 83% and a significant enabler to women's use of unskilled birth attendants [16,[26][27][28][29]. The literature also reveals healthcare professionals are aware of the occurrence of obstetric violence and associate it with poor working conditions of caregivers [30,31]. Women have reported physical abuse, humiliation, verbal abuse, neglect, and sometimes detention in health facilities [16,25,26].…”
Section: Introductionmentioning
confidence: 99%